Social enterprise in the context of educational institution: Lessons from Gontor, Indonesia - Daniar, .; Iswati, Sri; Fathullah Zarkasyi, Amal (Opción, 2019)
This paper describes the social enterprise model at pesantren Gontor which has gained wide recognition as a tool to overcome the independence of pesantren and the ability to integrate between welfare and education via a qualitative approach with a case study. The results of the study found that variation in the context of social enterprise management with pesantren values has differences with social companies in general. In conclusion, the social enterprise approach becomes an alternative and solution to open a new funding source for pesantren, and pesantren environment support for the implementation of the business model.